Pemanfaatan Ozon Sebagai Teknologi Berkelanjutan Daur Ulang Air Limbah Domestik Hotel X Lembang - Imam Rozali Fathar; A. Hadian Pratama Hamzah; Nurhasanah (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Domestic waste water comes from various daily human activities such as water from bathing or from toilets (feces and urine), used washing clothes, used washing cooking and eating utensils, leftover food or drinks in liquid form. WHO underlines the importance; management of human waste (feces and urine) safely, and disposed of safely. To reduce the negative impact on the environment, comprehensive and sustainable efforts are needed so that domestic wastewater can be disposed of safely or recycled so that it can be reused. This experiment was conducted in Lembang, West Bandung Regency, which took domestic wastewater from hotel X activities. The use of ozone in the wastewater recycling process is simpler than conventional chemical treatment processes that rely on chemical-based coagulants and flocculants, and has been shown to be able to reduce TSS. by 77.27%; Ammonia 96.17%; Oils & fats decreased 6%; Total Coliform 99.61% .. The use of ozone can be an option in the process of recycling domestic wastewater in a sustainable manner. environmental management is also related to the use of technology and methods in accordance with regional conditions and resource potential.